(untitled) (Journal of the College of Basic Education, 2025)
The oil resources in Qatar have attracted the attention of a number of foreign companies and their competition for it, especially British and American companies. The Anglo-Iranian Oil Company was able to control it in the early stages of its discovery, production and export. American companies then sought to participate in obtaining oil concessions in Qatari oil, but the Red Line Agreement signed in 1928 prevented them from doing so. However, American companies were trying to infiltrate Qatar and compete to gain a foothold until they were able to do so. Foreign competition was not limited to British and American companies only, but in later stages, Japanese companies also entered until the Qatari government was able in 1976 to own the shares of all Qatari companies in its country’s oil. This research aims to trace foreign competition for Qatari oil at an important stage in the history of the modern and contemporary Arabian Gulf.